(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2016)
This paper provides an analysis of the production and marketing of cheese cooperative dairy agribusiness Masiguito R.L. The aim is to analyze the cheese marketing chain identifying the links in the production chain. In turn, determine the agro industrial importance of cheese to the rural economy, assess the trading margins of the cooperative, and show the part that the livestock producer participates in the final price of cheese. The study methodology was qualitative document and a field visit. It has been found that the cooperative is operating into very dynamic domestic and international marketing channels. It was, also found that the cooperative operates in a market of high net profit margin. In addition, livestock producers involved in a chain of milk as suppliers with a high share of fluid milk and low participation, level of processing that is in phase, and this benefit is the production of cheese. REICE Vol.3(6) 2015: 216-237